2022
DOI: 10.1007/s00213-021-06053-w
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance during adulthood in a rat model of neonatal diffuse white matter injury

Abstract: Rationale Infants born prematurely risk developing diffuse white matter injury (WMI), which is associated with impaired cognitive functioning and an increased risk of autism spectrum disorder. Recently, our rat model of preterm diffuse WMI induced by combined fetal inflammation and postnatal hypoxia showed impaired motor performance, anxiety-like behaviour and autism-like behaviour in juvenile rats, especially males. Immunohistochemistry showed delayed myelination in the sensory cortex and impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 97 publications
(128 reference statements)
0
2
1
Order By: Relevance
“…Similarly to the short-delay paradigm, Cntnap2 -/rats had less omissions than their wildtype counterparts. This finding is not consistent across previous ASD 5-CSRTT studies [38,55]; however, the study that looked at WMI found a decrease in omission rate with a fixed visual distractor [46]. Despite this, the present study utilized an auditory distractor.…”
Section: Distraction Effect On 5-csrtt Performancecontrasting
confidence: 94%
See 2 more Smart Citations
“…Similarly to the short-delay paradigm, Cntnap2 -/rats had less omissions than their wildtype counterparts. This finding is not consistent across previous ASD 5-CSRTT studies [38,55]; however, the study that looked at WMI found a decrease in omission rate with a fixed visual distractor [46]. Despite this, the present study utilized an auditory distractor.…”
Section: Distraction Effect On 5-csrtt Performancecontrasting
confidence: 94%
“…Contrastingly, a neonatal white-matter injury (WMI) study did not find a significant difference in accuracy between treatment and wildtype counterparts during baseline training. WMI can lead to hindered cognitive processing and an increased risk of ASD [ 46 ]. These disagreeing results suggest that baseline acquisition is dependent on the ASD risk-factor models’ ability to learn a novel task, or different baseline protocols that can be employed in the 5-CSRTT [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation